Simultaneous differential scanning calorimetry - synchrotron X-ray powder diffraction: A powerful technique for physical form characterisation in pharmaceutical materials. - Clout, A; Buanz, A; Prior, T; Reinhard, C; Wu, Y; O'Hare, D; Williams, G; Gaisford, S (American Chemical Society, 2016)
We report a powerful new technique: hyphenating synchrotron X-ray powder diffraction (XRD) with differential scanning calorimetry (DSC). This is achieved with a simple modification to a standard laboratory DSC instrument, in contrast to previous reports which have involved extensive and complex modifications to a DSC to mount it in the synchrotron beam. The high-energy X-rays of the synchrotron permit the recording of powder diffraction patterns in as little as 2 s, meaning that thermally induced phase changes can be accurately quantified and additional insight on the nature of phase transitions obtained. Such detailed knowledge cannot be gained from existing laboratory XRD instruments, since much longer collection times are required. We demonstrate the power of our approach with two model systems, glutaric acid and sulfathiazole, both of which show enantiotropic polymorphism. The phase transformations between the low and high temperature polymorphs are revealed to be direct solid-solid processes, and sequential refinement against the diffraction patterns obtained permits phase fractions at each temperature to be calculated and unit cell parameters to be accurately quantified as a function of temperature. The combination of XRD and DSC has further allowed us to identify mixtures of phases which appeared phase-pure by DSC.